P647 Outcomes following the use of vedolizumab first line versus second line in Ulcerative Colitis: a single centre experience. (30th January 2023) - Almas, S; Al-Talib, I; Rahman, C; Ansari, M; Jones, J; Slater, J; King, D; De Silva, S
Abstract: Background: With the introduction of an increasing number of biological therapies for Ulcerative Colitis (UC), decisions regarding the sequencing of treatment continues to dominate current management strategies. In this single centre study, we assessed outcomes in patients with UC following first line treatment with the α4β7 integrin blocker vedolizumab (VDZ) therapy vs second line VDZ therapy following anti-Tumour Necrosis Factor (anti-TNF) exposure. Methods: All patients exposed to VDZ either first line or second line were identified via our Inflammatory Bowel Disease (IBD) registry. Data was collected retrospectively between June 2015 and June 2021. Baseline demographics, disease extent and activity scores, treatment continuation, and colectomy rates were analysed over a 52-week period. Results: A total of 100 patients were included in the study, age (median [IQR]) 52 [37-64] years; 52% male 48% female). VDZ as first line biologic included 38 patients, age (median [IQR]) 51 [34-65] years; 50% male and 50% female). The VDZ as second line (Ant-TNF exposed) group included 62 patients, age (median [IQR]) 52 [38-61] years; 53% male and 47% female). The Anti-TNF exposed group included infliximab 26 (43.3%), adalimumab 22 (35.5%), golimumab 12 (19.2%) and both infliximab and adalimumab 2 (3%). Disease extent (Montreal classification: E1:proctitis, E2: left-sided or E3: extensive disease) in the VDZ first line group (E1 (13.1%), E2 (61.6%) and E3 (26.3%)) versus VDZ second line (E1 (11.3%), E2 (61.3%) and E3 (27.4%)). In the VDZ first line group (38 cases), the outcomes at 52 weeks were: Treatment continuation 24 (63%), colectomy 2 (5%) and treatment switch in 12 (32%) to infliximab (4), Adalimumab (3), Ustekinumab (4) and Tofacitinib (1). In comparison, the Anti-TNF exposed group (62 cases) outcomes at 52 weeks were: Treatment continuation 46 (74%), colectomy 5 (8%) and treatment switch in 11 (18%) to Adalimumab (2), Ustekinumab (4) and Tofacitinib (5). A total of 7 of patients underwent colectomy during the 52 week follow up period. By 52 weeks, 94.8% (36/38) were colectomy free in the VDZ first line group versus 92% (57/62) in the anti-TNF exposed group, which was not statistically significant (odds ratio (OR) of having a colectomy in the VDZ1st line group vs the VDZ 2nd line group was 0.61(p=0.58)). Conclusion: Our study evaluated real-world treatment continuation and colectomy-free outcomes for VDZ as first and second line biologic therapy (Anti-TNF exposed) in patients with ulcerative colitis and confirmed its effectiveness in both treatment groups.